Eosinophilic Endomyocarditis Combined With Pericardial and Pleural Effusion - You, Sung-Hye (The Korean Society of Cardiology, 2009)
Eosinophilic endomyocarditis is a manifestation of hypereosinophilic syndrome, characterized by prolonged (>6 months), unexplained peripheral blood eosinophilia (>1,500 cells/mm(3)) with end-organ damage in unknown causes. We report a case of a 42-year-old patient who developed eosinophilic endomyocarditis following upper respiratory tract symptoms for 2 months. Additionally, endomyocarditis was combined with massive pleural effusion and pericardial effusion, which have not been reported in Korea.